Law and Sovereignty of the State in the Renegotiation of Freeport Contracts in Papua - Khamami Zada; Mustolih Mustolih; Diana Mutia Habibaty; Lukman Hakim; Desy Purwaningsih; Trini Diyani (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The mineral and coal mines have long been managed by foreign contracts between governments and foreigners. The position threatens the state's sovereignty over the wealth of natural resources. The study was to analyze the renege-management of Indonesia's Freeport mines in Papua. Socio-legal methods were used to analyze the renegotiation of Indonesia's Freeport management. The study found that according to the principle of state mastery over natural resources as a common property of Indonesian people's prosperity as in article 33 verses (3) constitution of 1945, the Indonesian government officially took over its 51-percent share of Freeport. It is part of an expression of national sovereignty over the management of its natural resources. With this position, Freeport's mining management is no longer based on a contract of work, but a Special Mining Business License which provides guarantees to business holders to have their licenses extended to provide certainty to mining business actors in conducting mining business in Indonesia.Keywords: Renegotiation; Freeport; State Sovereignity Hukum dan Kedaulatan Negara Dalam Renegosiasi Kontrak Freeport Di Papua Abstrak Pertambangan mineral dan batubara selama ini dikelola pihak asing berdasarkan kontrak antara pemerintah dan pihak asing. Posisi ini sesungguhnya mengancam kedaulatan negara atas kekeyaaan sumberdaya alam. Studi ini bertujuan untuk menganalisis renegosiasi pengelolaan tambang PT Freeport Indonesia di Papua. Metode socio-legal digunakan untuk menganalisis renegosiasi pengelolaan tambang PT Freeport Indonesia. Studi ini menemukan bahwa berdasarkan prinsip penguasaan negara atas sumberdaya alam sebagai common property bangsa Indonesia untuk kemakmuran rakyat sebagaimana pasal 33 ayat (3) Undang-Undang Dasar 1945, Pemerintah Indonesia secara resmi mengambil alih saham PT. Freeport Indonesia sebesar 51 %. Kebijakan ini merupakan bagian dari perwujudan kedaulatan negara atas pengelolaan sumberdaya alamnya. Dengan posisi ini, pengelolaan tambang Freeport bukan lagi berdasarkan kontrak karya, melainkan Izin Usaha Pertambangan Khusus yang memberikan jaminan kepada pemegang usaha untuk diperpanjang izinnya unutk memberikan kepastian kepada pelaku usaha pertambangan dalam melakukan bisnis pertambangan di Indonesia.Kata Kunci: Renegosiasi; Freeport; Kedaulatan Negara Закон и суверенитет государствапри пересмотре договоров Freeport в Папуа АннотацияДо настоящего времени управление добычей полезных ископаемых и угля осуществлялось иностранными сторонами на основании договоров между правительством и иностранными сторонами. Эта позиция фактически угрожает суверенитету государства над богатством природных ресурсов. Данное исследование направлено на анализ пересмотра условий руководства рудником компании Freeport Indonesia в Папуа. Социально-правовой метод был использован для анализа пересмотра условий руководства рудником компании Freeport Indonesia. Это исследование показало, что на основе принципа государственного контроля над природными ресурсами как общей собственностью индонезийского народа для процветания народа, как указано в пункте (3) статьи 33 Конституции 1945 года, правительство Индонезии официально приняло на себя акции из компании Freeport Indonesia на 51%. Эта политика является частью реализации государственного суверенитета над управлением своими природными ресурсами. С этой должностью управление горнодобывающей промышленностью Freeport больше не основывается на договоре на выполнение работ, а на специальной лицензии на горнодобывающий бизнес, которая предоставляет владельцам бизнеса гарантии продления их лицензий, чтобы обеспечить уверенность участников горнодобывающего бизнеса в ведении горнодобывающего бизнеса в Индонезии.Ключевые Слова: Пересмотр; Freeport; Государственный суверенитет